Presidencialismo democrático, crise política e as circunstâncias do impeachment - Lucas Azevedo Paulino (2021)
This doctoral thesis has the central purpose of understanding the presidential system of government and the institute of impeachment in constitutional democracies, with an emphasis on contexts of political crises. Based on an interdisciplinary methodological perspective, of constitutional theory combined with the institutionalist school of political science, this thesis intends to develop an in-depth analysis of the theoretical-normative assumptions, the history and empirical functioning of presidentialism and impeachment. It is concerned both with the principles that institutions should consider, on the one hand, such as democratic legitimacy and political stability, as with their effects and consequences, on the other hand. In this endeavor, this research adopts a middle-level normative perspective, of prescriptive institutional engineering sensitive to the context of real functioning. Based on these parameters, it was found that there is a gap between the constitutional normativity on impeachment and how it has been used politically to resolve political crises in contexts of instability and impasses between constitutional powers in multiparty presidential democracies. Democratic presidentialism is defined by the separation of powers between the executive and the legislature, with independence from the origin of the mandates of its members and from survival. The only chance of early dismissal of the president is through an impeachment, the legal nature of which can be described as a constitutional law sanction that only can be justified when employed against presidents who commit high constitutional offenses. It has been used in a more flexible and politicized way, against unpopular presidents who fail to maintain good relations with the legislature. This practice represents a distortion both presidentialism and impeachment. This unwelcomed distortion is due to the historical origin and tradition of the institute in dominantlegislative models, which disregarded the development of a system of organized parties, and entrusted the responsibility for the process and judgment to bodies that operate in a predominantly partisan and, therefore, partial way. Nevertheless, impeachment is an asymmetric procedure: parliamentarians indirectly remove a directly elected president. If there is no just cause to try the president, there is a problem of democratic legitimacy. For this reason, in the end, it considers the need for reform proposals both to improve the institutional design of impeachment, as presidential removal alternatives in political crises contexts without the existence of impeachable offenses.